A Quality Improvement Initiative to Increase Hand Hygiene Awareness and Compliance in a Neonatal Intensive Care Unit in Haiti. (28th June 2020) - Deshommes, Theony; Nagel, Christian; Tucker, Richard; Dorcélus, Lindsay; Gautier, Jacqueline; Koster, Michael P; Lechner, Beatrice E
Abstract: Introduction: Healthcare-associated infections (HCAI) are major causes of morbidity, mortality, increased lengths of stay and are an economic burden on healthcare systems in resources-limited settings. This is especially true for neonates, who are more susceptible with underdeveloped immune systems. Hand hygiene (HH) is a key weapon against HCAI, yet globally, HH compliance remains substandard. This study sought to determine the compliance with HH among healthcare workers (HCWs) in a children's hospital neonatal intensive care unit (NICU) in Haiti. Methods: A HH educational intervention was performed in the NICU, including lectures and posters. Pre- and post-intervention HH data were collected on HCWs and parents using the World Health Organization '5 Moments for HH'. Data were analyzed using standard statistical analysis. Results: HH increased in all HCW roles but not in parents. Correct HH increased in all groups, including parents. HH was more likely to occur prior to patient contact than after patient contact. Correct HH was more likely to occur with alcohol-based hand rub than with soap and water. Conclusion: This study demonstrates that an inexpensive and simple intervention can significantly increase HH compliance in a resource-limited NICU, which may lead to decreased rates of hospital-acquired sepsis. Parents, however, due to cultural norms as well as literacy and language barriers, need targeted educational interventions distinct from those that HCW benefit from.